Liliendaal declaration on agriculture and food security\n (CARICOM Secretariat GeorgetownGY, 2013)
Affirms the Heads of Government of the Caribbean Community commitment to the agricultural sector as one of the drivers of economic growth and poverty alleviation.
Issued at the Thirtieth Meeting of the Conference of Heads of Government of the Caribbean Community, Liliendaal, Guyana, 2-5 July 2009.\n